2019
DOI: 10.1177/1076029619889406
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pharmacological Profiles of Various Bovine, Ovine, and Porcine Heparins

Abstract: Unfractionated heparin is the first anticoagulant drug and has been successfully used clinically for over 80 years. Heparin and its analogues are used during surgery and dialysis and are often used to coat indwelling catheters and other devices where the vascular system is exposed. Most of the heparins used clinically are derived from porcine intestinal mucosa. However, heparins have also been manufactured from tissues of other mammalian species such as cows and sheep. Recently there have been attempts to gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…However, it should be noted that heparin contains other 3-O-sulfated sequences that might constitute lower-affinity sequences, which we suggest might have anticoagulant activity when present at high concentration. It is also notable that the nature of the antithrombin-binding sequence varies according to species and the organ from which the heparin was isolated (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that heparin contains other 3-O-sulfated sequences that might constitute lower-affinity sequences, which we suggest might have anticoagulant activity when present at high concentration. It is also notable that the nature of the antithrombin-binding sequence varies according to species and the organ from which the heparin was isolated (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…A previous publication has reported on the comparison of UFHs and LMWHs produced by using mucosal tissue of bovine, ovine and porcine origins. 18 Additional publication provide evidence of the equivalence of bovine and porcine UFHs at potency-adjusted levels. 32 It is noteworthy that, the bovine heparin preparations exhibit a lower potency in comparison to porcine heparin at equivalent mass levels.…”
Section: Discussionmentioning
confidence: 99%
“…As the U.S. heparin supply is dependent on Chinese manufacturers and up to 70% of the U.S. heparin is imported from China, the U.S. government is concerned on the dependence on one source and the potential impact of its shortage on patient usage. 18 In this study, we projected that, BMH, OMH and PMH have comparable PS neutralization profiles when administered at equi-gravimetric dosages. However, potency equated BMH may require higher amount of PS to be completely neutralized.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Mutations affecting the biosynthesis of heparan sulphate proteoglycans are implicated in multiple diseases including Simpson-Golabi-Behmel syndrome and Ehlers-Danlos syndrome [42]. Most commercial heparin production is derived from pig intestine or bovine lungs [44,45]. Multiple studies have shown that heparin and low-molecular-weight heparin (LMWH) appear to prolong survival in patients with cancer [46][47][48][49].…”
Section: Heparanasementioning
confidence: 99%